Grade A thermal insulation gypsum board

By combining the modified silane coupling agent and modified starch, the insulation and mechanical properties of the gypsum board are enhanced, and the problem of insufficient insulation performance in special seasons is solved, achieving better insulation effect and moisture-proof performance.

CN118345988BActive Publication Date: 2024-12-27JASON PLASTERBOARD JIAXING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410351280.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2024-12-27
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

The existing gypsum board has insufficient insulation performance during special seasons, which can easily lead to mold and damp indoor items, and other equipment is required to be used together.

Method used

The surface of the glass fiber alkali-resistant grid cloth is treated with a modified silane coupling agent, and combined with other substances is combined with the interface modifier, combined with the modified starch, and the insulation type paper-surface gypsum board is prepared to enhance its insulation. Performance and mechanical properties.

Benefits of technology

It significantly reduces the thermal conductivity of gypsum board, increases fracture load, improves moisture resistance, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118345988B_ABST
    Figure CN118345988B_ABST
Patent Text Reader

Abstract

The invention discloses a thermal insulation paper-faced gypsum board, which relates to the technical field of gypsum board preparation, including a gypsum core material, wherein the upper and lower surfaces of the gypsum core material are respectively solidified with a glass fiber alkali-resistant mesh cloth with surface treatment; and a face paper, wherein the face paper is respectively bonded to the upper and lower surfaces of the gypsum core material; the surface treatment of the glass fiber alkali-resistant mesh cloth is to coat the surface of the glass fiber alkali-resistant mesh cloth with an interface modifier, wherein the interface modifier includes a modified silane coupling agent, and the structure thereof includes at least siloxane, hydroxyl, alkane group, olefin group, and cyclic group. The thermal insulation paper-faced gypsum board provided by the invention has better thermal insulation performance, and its thermal conductivity coefficient is significantly reduced; the mechanical properties are beneficially changed, and the load required for fracture is significantly increased; and it has more excellent moisture-proof performance, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with the application date of February 1, 2023, application number 202310050262.8, and invention name “Thermal insulation paper-faced gypsum board”. Technical Field

[0002] The invention belongs to the technical field of gypsum board preparation, and in particular relates to a heat-insulating paper-faced gypsum board. Background Art

[0003] Gypsum board is a material made of building gypsum as the main raw material. It is a building material with light weight, high strength, thin thickness, easy processing, and good sound insulation, heat insulation and fire resistance. It is one of the new lightweight panels that are currently being developed. Gypsum board has been widely used in interior partitions, wall coverings, ceilings, sound-absorbing panels, ground base panels and various decorative panels in various buildings such as residences, office buildings, shops, hotels and industrial plants.

[0004] In the prior art, gypsum board materials are single, and in some special seasons, such as the Great Cold, the Lesser Cold, the plum rain season, etc., the thermal insulation performance of general gypsum board is not very high. For example, in the plum rain season, it is easy to cause indoor items to become moldy and damp, and other equipment is required for use. Summary of the invention

[0005] The purpose of the present invention is to provide a thermal insulation type gypsum board, which has better thermal insulation performance and its thermal conductivity is significantly reduced; the mechanical properties are beneficially changed, and the load required for breaking is significantly increased; and it has more excellent moisture-proof performance and broad application prospects.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] A heat-insulating gypsum board, comprising a gypsum core material, wherein the upper and lower surfaces of the gypsum core material are respectively solidified with surface-treated glass fiber alkali-resistant mesh cloth;

[0008] and a face paper, the face paper being bonded to the upper surface layer and the lower surface layer of the gypsum core material respectively;

[0009] The surface treatment of the above-mentioned glass fiber alkali-resistant mesh cloth is to coat the surface of the glass fiber alkali-resistant mesh cloth with an interface modifier, and the above-mentioned interface modifier includes a modified silane coupling agent, and its structure at least includes siloxane, hydroxyl, alkane group, olefin group, and cyclic group. The present invention uses perillyl alcohol to modify the silane coupling agent, and then uses it as an interface modifier component, and then uses it in combination with other substances to coat the surface of the glass fiber alkali-resistant mesh cloth. The prepared thermal insulation paper-faced gypsum board has more excellent thermal insulation performance, and its thermal conductivity shows a significant decrease; and the mechanical properties of the gypsum board are further enhanced, and the load required for its transverse and longitudinal fracture is significantly increased. The reason may be that the modified silane coupling agent and other components are attached to the surface of the glass fiber alkali-resistant mesh cloth, and the introduced active functional groups better improve the interface problem, can better reduce or reduce the internal stress changes of the gypsum board caused by the impact force changes, prevent the expansion of cracks, and embody more excellent mechanical properties.

[0010] In a specific embodiment, the chemical structure of the modified silane coupling agent is shown in Formula I:

[0011] I.

[0012] In a specific embodiment, the interface modifier raw materials include, by weight, 0.5-2 parts of styrene aminotrimethoxysilane, 0.1-0.8 parts of γ-aminopropyltriethoxysilane, 0.5-1.5 parts of modified silane coupling agent, 0.8-1.2 parts of glacial acetic acid, and 95-98 parts of water.

[0013] The present invention further discloses a method for preparing the above-mentioned interface modifier, comprising:

[0014] Take half of the glacial acetic acid and add water, keep the pH to 1.8-2.4, then slowly drop styrene aminotrimethoxysilane, and stir thoroughly for 25-40 minutes; then slowly add γ-aminopropyltriethoxysilane and modified silane coupling agent, and stir for 50-70 minutes to obtain a pre-hydrolysis solution;

[0015] Take the remaining amount of glacial acetic acid and add water to adjust the pH to 4-5. After stirring for 20-40 minutes, slowly add the pre-hydrolysis solution dropwise and stir for 60-70 minutes to obtain the interface modifier.

[0016] In a specific embodiment, the surface treatment of the glass fiber alkali-resistant mesh cloth is specifically performed by coating the glass fiber alkali-resistant mesh cloth with an interface modifier and drying the surface.

[0017] It should be noted that the coating amount of the interface modifier is 0.1~0.2g / cm 2 .

[0018] In a specific embodiment, the raw materials of the gypsum core material include building gypsum powder and aerogel.

[0019] In a specific embodiment, the aerogel is selected from one or more of silica aerogel, alumina aerogel and carbon aerogel.

[0020] In a specific embodiment, the particle size of the aerogel is 20-200 μm.

[0021] In a specific embodiment, the raw material of the gypsum core material further includes starch.

[0022] The raw materials of the above-mentioned thermal insulation gypsum board include: by weight, 70-90 parts of building gypsum powder, 40-60 parts of water, 0.05-0.5 parts of aerogel, 1-3 parts of surface-treated glass fiber alkali-resistant mesh cloth, 0.2-1.5 parts of starch, 0.05-0.5 parts of foaming agent, and 0.1-0.8 parts of water reducer.

[0023] In a specific embodiment, the foaming agent is selected from one or more of ammonium lauryl sulfate, sodium bicarbonate and ammonium bicarbonate.

[0024] In a specific embodiment, the water reducing agent is a polycarboxylic acid water reducing agent.

[0025] In a specific embodiment, the average longitudinal breaking load of the thermal insulation gypsum board is >550N, and the average transverse breaking load is >215N; more preferably, the average longitudinal breaking load is >590N, and the average transverse breaking load is ≥260N.

[0026] In a specific implementation, the thermal conductivity of the thermal insulation gypsum board is 0.07-0.11 W / (m·K).

[0027] Another object of the present invention is to disclose a method for preparing a modified silane coupling agent shown in Formula I, comprising: preparing the modified silane coupling agent by subjecting triethoxysilane to a hydrosilylation reaction using perillyl alcohol.

[0028] Furthermore, the preparation method of the modified silane coupling agent is specifically as follows:

[0029] Dissolve perillyl alcohol in toluene, heat to 50-60°C, add karstedt catalyst and continue stirring for 40-60 minutes; then add triethoxysilane to the constant pressure dropping funnel, and then slowly drop it into the solution. After the dropwise addition is completed, react at a constant temperature of 75-80°C for 20-25 hours; filter while hot, cool to room temperature, rotary evaporate, dry, and then recrystallize with ethanol to obtain a modified silane coupling agent;

[0030] It should be noted that the mass ratio of perillyl alcohol to triethoxysilane is 1:0.3~0.45; the solid-liquid ratio of perillyl alcohol to toluene is 1g:40~50mL; and the solid-liquid ratio of perillyl alcohol to karstedt catalyst is 1.6g:0.12~0.2mL.

[0031] The present invention further discloses a method for preparing the above-mentioned thermal insulation gypsum board, comprising:

[0032] S1: Mix building gypsum powder, starch, foaming agent and water reducing agent and stir them evenly to obtain a mixture; Mix aerogel and water and stir them to obtain a mixed liquid; Mix the mixture with the mixed liquid and stir them evenly to obtain a mixed slurry;

[0033] S2: Lay the first portion of the surface-treated alkali-resistant glass fiber mesh cloth in the mold with the face paper laid according to the size, pour 1 / 3 of the mixed slurry obtained in step S1 into the mold, flatten it, and finally set and demould to obtain the upper surface layer;

[0034] S3: Lay a second portion of surface-treated alkali-resistant glass fiber mesh cloth in the mold on which the face paper has been laid according to the size, pour 1 / 3 of the mixed slurry obtained in step S1 into the mold, flatten it, and finally set and demould to obtain the lower surface layer;

[0035] S4: According to the thickness requirements of the gypsum board, assemble and fix the upper surface layer and the lower surface layer in the mold, take the remaining mixed slurry for pouring, and after final setting and demoulding, let it stand for curing, and then dry it to obtain the thermal insulation paper-faced gypsum board.

[0036] More preferably, in the preparation process of thermal insulation gypsum board, modified starch is used to replace starch; the modified starch is obtained by cross-linking and modifying oxidized corn starch with epichlorohydrin and then grafting and modifying with BA, AM, and functional monomer S. The present invention first uses pyrazole-3,5-dicarboxylic acid monohydrate and glycidyl acrylate to prepare functional monomers through epoxy ring-opening reaction, and then compounding with other monomers to graft and polymerize the oxidized corn starch. The prepared modified starch has more excellent bonding properties and its bonding strength is significantly improved; at the same time, it is applied to the preparation process of gypsum board, which can effectively improve the mechanical properties of gypsum board, and the thermal insulation ability is further enhanced, and the moisture-proof ability is also improved. The reason may be that the functional monomer grafted modified starch prepared by the present invention may introduce certain side chains or functional side groups into its structure, and the prepared modified starch has more chemical bonds, forming a more stable cross-linked network structure, showing more excellent bonding ability, and can better play a bonding role in the gypsum board structure, thereby improving the comprehensive performance of the gypsum board.

[0037] In a specific embodiment, the functional monomer S is obtained by chemically bonding pyrazole-3,5-dicarboxylic acid monohydrate and glycidyl acrylate.

[0038] Furthermore, the preparation method of the modified starch is specifically as follows:

[0039] Take pyrazole-3,5-dicarboxylic acid monohydrate and 1,2-dichloroethane, mix them, stir them at room temperature for 5-10 minutes, then slowly add glycidyl acrylate, after the addition is complete, heat to 50-60°C, stir and react for 4-6 hours; then remove the reaction solvent and excess glycidyl acrylate, recrystallize the product with acetone, and then place it at 50-60°C and vacuum dry for 24-36 hours to obtain functional monomer S;

[0040] Take the first batch of oxidized corn starch, add water to form a 45~55wt% starch emulsion, add epichlorohydrin, react at 25~35℃ for 2~4h, then add the second batch of oxidized corn starch and water mixture, continue to react for 0.5~1.5h to obtain a cross-linked starch emulsion; then under the protection of nitrogen, add initiator APS-NaHSO3, add SDS and PVA after 20~40min, react for 15~25min, then add mixed monomers, react at 65~75℃ for 2~4h, gelatinize at 75~85℃ for 20~40min, and cool to room temperature to obtain modified starch.

[0041] In a specific embodiment, the solid-to-liquid ratio of pyrazole-3,5-dicarboxylic acid monohydrate and 1,2-dichloroethane is 0.25-0.4 g:1 mL; the molar ratio of glycidyl acrylate to pyrazole-3,5-dicarboxylic acid monohydrate is 1.3-1.5:1.

[0042] In a specific embodiment, the mass ratio of the second batch of oxidized corn starch to water is 1.4-1.6:1; and the amount of the second batch of oxidized corn starch added is 23-27 wt % of the first batch of oxidized corn starch.

[0043] In a specific embodiment, the amount of epichlorohydrin added is 0.05-0.2wt% of the oxidized corn starch; the amount of mixed monomer added is 6-8wt% of the oxidized corn starch; and the molar ratio of BA, AM and functional monomer S is 1:0.4-0.6:0.2-0.4.

[0044] In a specific embodiment, the mass ratio of APS to NaHSO3 in the initiator is 1:1~1.2; the amount of the initiator used is 0.8~1.5wt% of the oxidized corn starch; the amount of SDS added is 1~2wt% of the oxidized corn starch; and the amount of PVA added is 12~15wt% of the oxidized corn starch.

[0045] In a specific embodiment, the viscosity of the modified starch is 800-1000 mPa·s.

[0046] The invention also discloses the use of the modified silane coupling agent shown in formula I in preparing the thermal insulation type paper-faced gypsum board.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The present invention uses perillyl alcohol to modify the silane coupling agent, and then uses it as an interface modifier component, and then uses it in combination with other substances to perform surface treatment on the glass fiber alkali-resistant mesh cloth. The prepared thermal insulation paper-faced gypsum board has more excellent thermal insulation performance, and the mechanical properties of the gypsum board are further enhanced, and the load required for its transverse and longitudinal fracture is significantly increased. The present invention first uses pyrazole-3,5-dicarboxylic acid monohydrate and glycidyl acrylate to prepare a functional monomer through an epoxy ring-opening reaction, and then uses other monomers to perform graft polymerization modification on oxidized corn starch. The prepared modified starch has more excellent bonding properties. It is applied to the preparation process of paper-faced gypsum board, which can effectively improve the mechanical properties of the gypsum board, and the thermal insulation capacity is further enhanced, and the moisture-proof ability is also improved.

[0049] Therefore, the present invention provides a thermal insulation type gypsum board, which has better thermal insulation performance and its thermal conductivity is significantly reduced; the mechanical properties are beneficially changed, and the load required for breaking is significantly increased; and it has more excellent moisture-proof performance and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 These are the infrared spectrum test results of the modified starch prepared in Examples 5 and 8 of the present invention. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods:

[0052] The water reducer used in the embodiment of the present invention is a polycarboxylic acid water reducer purchased from Tangshan Yonghe Water Treatment Agent Co., Ltd., and the model is BF-808L polycarboxylic acid high performance water reducer.

[0053] The oxidized corn starch used in the examples of the present invention was purchased from Shandong Ruiying Modified Starch Co., Ltd.

[0054] Embodiment 1:

[0055] A thermal insulation gypsum board, comprising raw materials as follows: by weight, 80 parts of building gypsum powder, 50 parts of water, 0.25 parts of aerogel (silicon dioxide aerogel, with an average particle size of 120 μm), 2 parts of surface-treated glass fiber alkali-resistant mesh cloth, 1 part of starch, 0.3 parts of a foaming agent (ammonium dodecyl sulfate), and 0.4 parts of a water reducer.

[0056] Surface treatment of glass fiber alkali-resistant mesh cloth: the specific operation is: take the interface modifier to coat the glass fiber alkali-resistant mesh cloth and dry it; the coating amount is 0.14g / cm 2 .

[0057] An interface modifier comprises: by weight, 1.2 parts of styrene aminotrimethoxysilane, 0.4 parts of gamma-aminopropyltriethoxysilane, 1 part of modified silane coupling agent, 1 part of glacial acetic acid, and 97 parts of water.

[0058] Preparation of interfacial modifier:

[0059] Take half of the glacial acetic acid and add water, keep the pH to 2.2, then slowly drop styrene aminotrimethoxysilane, and stir thoroughly for 35 minutes; then slowly add γ-aminopropyltriethoxysilane and modified silane coupling agent, and stir for 60 minutes to obtain a pre-hydrolysis solution;

[0060] The remaining amount of glacial acetic acid was added to water to adjust the pH to 4.5. After stirring for 35 minutes, the pre-hydrolysis solution was slowly added dropwise and stirred for 65 minutes to obtain the interface modifier.

[0061] Preparation of the above modified silane coupling agent:

[0062] Dissolve perillyl alcohol in toluene (solid-liquid ratio is 1g:45mL), heat to 56°C, add karstedt catalyst (solid-liquid ratio of perillyl alcohol to karstedt catalyst is 1.6g:0.16mL), and continue stirring for 55min; then add triethoxysilane (mass ratio of perillyl alcohol to triethoxysilane is 1:0.38) to the constant pressure dropping funnel, and then slowly drop it into the solution. After the dropwise addition is completed, react at a constant temperature of 80°C for 24h; filter while hot, cool to room temperature, rotary evaporate, dry, and then recrystallize with ethanol to obtain a modified silane coupling agent (structure shown below); 1 H NMR (400 MHz, CDCl3): δ: 5.51 (dd, 1H, C=C H ), 4.18 (s, 2H, -C H 2), 3.85 (m, 6H, Si-OC H 2), 1.46, 1.38 (m, 2H, -C H ), 1.31~2.24 (m, 6H, -C H 2), 1.24(t, 9H, Si-O-CH2-C H 3), 0.96 (d, 3H, -C H 3), 0.68, 0.41 (m, 2H, Si-C H 2).

[0063]

[0064] Preparation of the above-mentioned thermal insulation gypsum board:

[0065] S1: Mix building gypsum powder, starch, foaming agent and water reducing agent and stir them evenly to obtain a mixture; Mix aerogel and water and stir them to obtain a mixed liquid; Mix the mixture with the mixed liquid and stir them evenly to obtain a mixed slurry;

[0066] S2: Lay the first portion of the surface-treated alkali-resistant glass fiber mesh cloth in the mold with the face paper laid according to the size, pour 1 / 3 of the mixed slurry obtained in step S1 into the mold, flatten it, and finally set and demould to obtain the upper surface layer;

[0067] S2: Lay a second portion of surface-treated alkali-resistant glass fiber mesh cloth in the mold on which the face paper has been laid according to the size, pour 1 / 3 of the mixed slurry obtained in step S1 into the mold, flatten it, and finally set and demould to obtain the lower surface layer;

[0068] S3: According to the thickness requirement of the gypsum board, assemble and fix the upper surface layer and the lower surface layer in the mold, take the remaining mixed slurry for pouring, and after final setting and demoulding, let it stand for curing, and then dry it to obtain the thermal insulation paper-faced gypsum board.

[0069] Embodiment 2:

[0070] The preparation of the modified silane coupling agent is the same as that in Example 1.

[0071] A thermal insulation gypsum board, comprising raw materials as follows: by weight, 74 parts of building gypsum powder, 46 parts of water, 0.15 parts of aerogel (alumina aerogel, with an average particle size of 108 μm), 2 parts of surface-treated glass fiber alkali-resistant mesh cloth, 0.8 parts of starch, 0.15 parts of a foaming agent (sodium bicarbonate), and 0.2 parts of a water reducing agent.

[0072] Surface treatment of glass fiber alkali-resistant mesh cloth: the specific operation is: take the interface modifier to coat the glass fiber alkali-resistant mesh cloth and dry it; the coating amount is 0.11g / cm 2 .

[0073] The above-mentioned interface modifier includes: in parts by weight, 0.7 parts of styrene aminotrimethoxysilane, 0.2 parts of γ-aminopropyltriethoxysilane, 0.6 parts of modified silane coupling agent, 0.8 parts of glacial acetic acid, and 98 parts of water.

[0074] The preparation of the interface modifier is the same as that in Example 1.

[0075] The preparation of the above-mentioned thermal insulation gypsum board is the same as that in Example 1.

[0076] Embodiment 3:

[0077] The preparation of the modified silane coupling agent is the same as that in Example 1.

[0078] A thermal insulation gypsum board, comprising raw materials, by weight, 88 parts of building gypsum powder, 58 parts of water, 0.45 parts of aerogel (carbon aerogel, with an average particle size of 89 μm), 2 parts of surface-treated glass fiber alkali-resistant mesh cloth, 1.4 parts of starch, 0.4 parts of a foaming agent (ammonium bicarbonate), and 0.7 parts of a water reducer.

[0079] Surface treatment of glass fiber alkali-resistant mesh cloth: the specific operation is: take the interface modifier to coat the glass fiber alkali-resistant mesh cloth and dry it; the coating amount is 0.17g / cm 2 .

[0080] The above-mentioned interface modifier includes: in parts by weight, 1.6 parts of styrene aminotrimethoxysilane, 0.6 parts of γ-aminopropyltriethoxysilane, 1.3 parts of modified silane coupling agent, 1.2 parts of glacial acetic acid, and 96 parts of water.

[0081] The preparation of the interface modifier is the same as that in Example 1.

[0082] The preparation of the above-mentioned thermal insulation gypsum board is the same as that in Example 1.

[0083] Embodiment 4:

[0084] The preparation of the modified silane coupling agent is the same as that in Example 1.

[0085] A thermal insulation gypsum board, comprising raw materials, by weight, 84 parts of building gypsum powder, 55 parts of water, 0.5 parts of aerogel (silicon dioxide aerogel, with an average particle size of 120 μm), 2 parts of surface-treated glass fiber alkali-resistant mesh cloth, 0.9 parts of starch, 0.42 parts of a foaming agent (ammonium dodecyl sulfate), and 0.58 parts of a water reducer.

[0086] Surface treatment of glass fiber alkali-resistant mesh cloth: the specific operation is: take the interface modifier to coat the glass fiber alkali-resistant mesh cloth and dry it; the coating amount is 0.17g / cm 2 .

[0087] The above-mentioned interface modifier includes: in parts by weight, 1.2 parts of styrene aminotrimethoxysilane, 0.6 parts of γ-aminopropyltriethoxysilane, 1.2 parts of modified silane coupling agent, 0.9 parts of glacial acetic acid, and 97 parts of water.

[0088] The preparation of the interface modifier is the same as that in Example 1.

[0089] The preparation of the above-mentioned thermal insulation gypsum board is the same as that in Example 1.

[0090] Embodiment 5:

[0091] The preparation of the modified silane coupling agent is the same as that in Example 1.

[0092] A thermal insulation gypsum board is different from Example 1 in that an equal weight portion of modified starch is used to replace starch.

[0093] The surface treatment of the glass fiber alkali-resistant mesh cloth is the same as that in Example 1. The interface modifier and its preparation are the same as those in Example 1.

[0094] The preparation of the above-mentioned thermal insulation gypsum board is the same as that in Example 1.

[0095] Preparation of the above modified starch:

[0096] Take pyrazole-3,5-dicarboxylic acid monohydrate and 1,2-dichloroethane (solid-liquid ratio is 0.32g:1mL), stir at room temperature for 8min, then slowly add glycidyl acrylate (molar ratio to pyrazole-3,5-dicarboxylic acid monohydrate is 1.5:1), after the addition is complete, heat to 56°C, stir and react for 5h; then remove the reaction solvent and excess glycidyl acrylate, recrystallize the product with acetone, and then place it at 55°C for vacuum drying for 24h to obtain functional monomer S; 1 H NMR (400 MHz, Acetone-d6) δ: 7.03(1H, -CH), 6.51, 6.15, 5.86(3H, CH=CH2), 4.0~4.58(4H, -CH2), 4.70(m, 1H, -CH);

[0097] Take the first batch of oxidized corn starch, add water to make a 52wt% starch emulsion, add epichlorohydrin (the amount added is 0.16wt% of the oxidized corn starch), react at 30°C for 3h, then add a mixture of the second batch of oxidized corn starch (the amount added is 25.6wt% of the first batch of oxidized corn starch) and water (the mass ratio of the two is 1.5:1), and continue to react for 1h to obtain a cross-linked starch emulsion; then, under the protection of nitrogen, add the initiator APS-NaHSO3 (the mass ratio of APS to NaHSO3 is 1:1.1, using After 30 minutes, SDS (added amount is 1.5wt% of oxidized corn starch) and PVA (added amount is 13.6wt% of oxidized corn starch) were added and reacted for 20 minutes. Then, mixed monomers (BA, AM and functional monomer S, the molar ratio of the three is 1:0.48:0.32, and the added amount is 7.2wt% of oxidized corn starch) were added, and the reaction was carried out at 70°C for 3 hours. The temperature was raised to 80°C for gelatinization for 30 minutes, and the modified starch (viscosity 960mPa·s) was obtained by cooling to room temperature.

[0098] Embodiment 6:

[0099] The preparation of the modified silane coupling agent is the same as that in Example 5.

[0100] A thermal insulation gypsum board is different from Example 5 in that the modified starch is prepared in this example.

[0101] The surface treatment of the glass fiber alkali-resistant mesh cloth is the same as that in Example 5. The interface modifier and its preparation are the same as those in Example 5.

[0102] The preparation of the above-mentioned thermal insulation paper-faced gypsum board is the same as that in Example 5.

[0103] The preparation of the modified starch described above is different from that of Example 5 in that: the amount of epichlorohydrin added is 0.1wt% of the oxidized corn starch; the amount of mixed monomer added is 6.4wt% of the oxidized corn starch; and the molar ratio of BA, AM and functional monomer S is 1:0.42:0.25.

[0104] Embodiment 7:

[0105] A thermal insulation gypsum board is different from Example 5 in that the surface treatment of the glass fiber alkali-resistant mesh cloth is the same as that of this example.

[0106] The surface treatment of the glass fiber alkali-resistant mesh cloth is different from that of Example 5 in that the interface modifier is prepared in this example. The interface modifier is different from that of Example 5 in that triethoxysilane is used instead of the modified silane coupling agent. The preparation method of the interface modifier is the same as that of Example 5.

[0107] The preparation of the above-mentioned thermal insulation paper-faced gypsum board is the same as that in Example 5.

[0108] The preparation of modified starch is the same as that in Example 5.

[0109] Embodiment 8:

[0110] A thermal insulation gypsum board is different from Example 7 in that the modified starch is prepared in this example.

[0111] The surface treatment of the glass fiber alkali-resistant mesh cloth is the same as that in Example 7. The interface modifier and its preparation are the same as those in Example 7.

[0112] The preparation of the above-mentioned thermal insulation paper-faced gypsum board is the same as that in Example 7.

[0113] The preparation of the modified starch described above is different from that of Example 7 in that an equimolar amount of AM is used to replace the functional monomer S.

[0114] Embodiment 9:

[0115] A thermal insulation gypsum board is different from Example 1 in that the surface treatment of the glass fiber alkali-resistant mesh cloth is the same as that of this example.

[0116] The surface treatment of the glass fiber alkali-resistant mesh cloth is different from that of Example 1 in that the interface modifier is prepared in this example. The interface modifier is different from that of Example 1 in that triethoxysilane is used to replace the modified silane coupling agent. The preparation method of the interface modifier is the same as that of Example 1.

[0117] The preparation of the above-mentioned thermal insulation gypsum board is the same as that in Example 1.

[0118] Test Example 1:

[0119] Infrared characterization

[0120] The test was conducted using the potassium bromide tablet method using a Fourier transform infrared spectrometer with a wavelength range of 4000~500cm -1 .

[0121] The modified starch prepared in Example 5 and Example 8 was tested as above, and the results are as follows: Figure 1 As shown in the figure, compared with the infrared spectrum of the modified starch prepared in Example 8, in the infrared test results of the modified starch prepared in Example 5, 1605cm -1 The characteristic absorption peaks of C=C bonds or C=N bonds appear nearby, indicating that the modified starch in Example 5 is successfully prepared.

[0122] Test Example 2:

[0123] Thermal conductivity determination

[0124] The test method is carried out in accordance with the standard specified in GB / T 10295-2008 "Determination of steady-state thermal resistance and related properties of insulation materials - Heat flow meter method".

[0125] The above test was performed on the thermal insulation paper-faced gypsum boards prepared in Examples 1 to 9, and the results are shown in Table 1:

[0126] Table 1 Thermal conductivity test results

[0127]

[0128] From the data analysis in Table 1, it can be seen that the thermal conductivity of the thermal insulation gypsum board prepared in Example 1 is significantly lower than that in Example 9, indicating that the use of perillyl alcohol modified silane coupling agent as a component of the interface modifier for the surface treatment of glass fiber alkali-resistant mesh cloth, the treated glass fiber alkali-resistant mesh cloth is used for the preparation of gypsum board, which can effectively improve the thermal conductivity of the gypsum board, and its thermal conductivity is significantly reduced, and the thermal insulation effect is enhanced. The effect of Example 5 is better than that of Example 1, and the effect of Example 7 is better than that of Examples 8-9, indicating that the functional monomer grafted modified starch prepared by the present invention is used in the preparation process of gypsum board, which can further improve the thermal insulation performance of gypsum board.

[0129] Test Example 3:

[0130] The test was conducted on the physical and mechanical properties of gypsum board samples with reference to the standards specified in GB / T 9775-2008.

[0131] The above test was performed on the thermal insulation gypsum boards prepared in Examples 1 to 9, and the results are shown in Table 2:

[0132] Table 2 Physical and mechanical properties test results

[0133]

[0134] From the data analysis in Table 2, it can be seen that the average longitudinal and transverse breaking loads of the thermal insulation gypsum board prepared in Example 1 are significantly higher than those in Example 9, indicating that the use of perillyl alcohol modified silane coupling agent as a component of the interface modifier for the surface treatment of glass fiber alkali-resistant mesh cloth, and the treated glass fiber alkali-resistant mesh cloth for the preparation of gypsum board can effectively improve the mechanical properties of gypsum board, and its breaking load value is significantly increased. The effect of Example 5 is better than that of Example 1, and the effect of Example 7 is better than that of Examples 8-9, indicating that the functional monomer grafted modified starch prepared by the present invention is used in the preparation process of gypsum board, which can further improve the mechanical properties of gypsum board.

[0135] Test example 4:

[0136] Determination of moisture deflection

[0137] The test method is carried out in accordance with the standard specified in GB / T 9775-2008.

[0138] The above test was performed on the thermal insulation gypsum boards prepared in Examples 1 to 9, and the results are shown in Table 3:

[0139] Table 3 Test results of moisture deflection

[0140]

[0141] From the data analysis in Table 3, it can be seen that the moisture deflection of the thermal insulation gypsum board prepared in Example 1 is equivalent to that of Example 9, indicating that the use of perillyl alcohol modified silane coupling agent as a component of the interface modifier for the surface treatment of glass fiber alkali-resistant mesh cloth, and the treated glass fiber alkali-resistant mesh cloth for the preparation of gypsum board does not have a negative impact on the moisture-proof performance of the gypsum board. The effect of Example 5 is better than that of Example 1, and the effect of Example 7 is better than that of Examples 8-9, indicating that the functional monomer grafted modified starch prepared by the present invention is used in the preparation process of gypsum board, which can further improve the moisture-proof performance of the gypsum board and significantly reduce the moisture deflection.

[0142] Test Example 5:

[0143] Bond strength determination

[0144] The test was carried out in accordance with the standard specified in GB / T 14074.10. Specifically, three birch boards with straight grain dimensions of 10×6×1cm were overlapped and bonded together with the sample to be tested, with a gluing area of ​​6×6cm, and dried to obtain the test piece. Then, the test piece was measured using an RCT-2TR universal mechanical testing machine with a tensile rate of 25mm / min.

[0145] The modified starches prepared in Example 5 and Example 8 were subjected to the above test, and the results are shown in Table 4:

[0146] Table 4 Bonding strength test results

[0147]

[0148] From the data analysis in Table 4, it can be seen that the bonding strength of the modified starch prepared in Example 5 is significantly better than that of Example 8, indicating that the modified starch prepared by grafting the functional monomer modified starch prepared by the present invention has more excellent adhesive properties and the bonding strength is significantly enhanced.

[0149] The conventional techniques in the above embodiments are prior arts known to those skilled in the art, and thus will not be described in detail here.

[0150] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A thermal insulation gypsum board, comprising a gypsum core material, wherein the upper and lower surfaces of the gypsum core material are respectively solidified with surface-treated glass fiber alkali-resistant mesh cloth; and a face paper, wherein the face paper is respectively bonded to the upper surface layer and the lower surface layer of the gypsum core material; The surface treatment of the glass fiber alkali-resistant mesh cloth is to coat the surface of the glass fiber alkali-resistant mesh cloth with an interface modifier, wherein the interface modifier includes a modified silane coupling agent, and the structure thereof includes at least siloxane, hydroxyl, alkane group, olefin group, and cyclic group. The chemical structure of the modified silane coupling agent is shown in Formula I: I; The raw material of the gypsum core material includes modified starch, which is obtained by cross-linking and modifying oxidized corn starch with epichlorohydrin and then grafting BA, AM and functional monomer S, wherein the functional monomer S is obtained by chemically bonding pyrazole-3,5-dicarboxylic acid monohydrate and glycidyl acrylate; The preparation of modified starch is specifically as follows: Take pyrazole-3,5-dicarboxylic acid monohydrate and 1,2-dichloroethane, mix them, stir them at room temperature for 5-10 minutes, then slowly add glycidyl acrylate, after the addition is complete, heat to 50-60°C, stir and react for 4-6 hours; then remove the reaction solvent and excess glycidyl acrylate, recrystallize the product with acetone, and then place it at 50-60°C and vacuum dry for 24-36 hours to obtain functional monomer S; Take the first batch of oxidized corn starch, add water to form a 45-55wt% starch emulsion, add epichlorohydrin, react at 25-35°C for 2-4h, then add a second batch of oxidized corn starch and water mixture, continue to react for 0.5-1.5h to obtain a cross-linked starch emulsion; then under the protection of nitrogen, add initiator APS-NaHSO3, add SDS and PVA after 20-40min, react for 15-25min, then add mixed monomers, react at 65-75°C for 2-4h, gelatinize at 75-85°C for 20-40min, and cool to room temperature to obtain modified starch; The solid-liquid ratio of pyrazole-3,5-dicarboxylic acid monohydrate and 1,2-dichloroethane is 0.25-0.4 g:1 mL; the molar ratio of glycidyl acrylate to pyrazole-3,5-dicarboxylic acid monohydrate is 1.3-1.5:1; The mass ratio of the second batch of oxidized corn starch to water is 1.4-1.6:1; the amount of the second batch of oxidized corn starch added is 23-27wt% of the first batch of oxidized corn starch; The amount of epichlorohydrin added is 0.05-0.2wt% of the oxidized corn starch; the amount of mixed monomer added is 6-8wt% of the oxidized corn starch; the molar ratio of BA, AM and functional monomer S is 1:0.4-0.6:0.2-0.4; The mass ratio of APS to NaHSO3 in the initiator is 1:1~1.2; the amount of initiator used is 0.8~1.5wt% of the oxidized corn starch; the amount of SDS added is 1~2wt% of the oxidized corn starch; and the amount of PVA added is 12~15wt% of the oxidized corn starch.

2. The thermal insulation gypsum board according to claim 1, characterized in that: The interface modifier raw materials include, by weight, 0.5-2 parts of styrene aminotrimethoxysilane, 0.1-0.8 parts of γ-aminopropyltriethoxysilane, 0.5-1.5 parts of modified silane coupling agent, 0.8-1.2 parts of glacial acetic acid, and 95-98 parts of water.

3. The thermal insulation gypsum board according to claim 1, characterized in that: The raw materials of the gypsum core material also include building gypsum powder and aerogel.

4. The thermal insulation gypsum board according to claim 3, characterized in that: The aerogel is selected from one or more of silica aerogel, alumina aerogel and carbon aerogel.

5. The thermal insulation gypsum board according to claim 1, characterized in that: The average longitudinal breaking load of the thermal insulation gypsum board is greater than 550N, and the average transverse breaking load is greater than 215N.